2017
DOI: 10.1210/en.2016-1839
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Metabolic Roles of Peripheral Serotonin

Abstract: Serotonin (5-hydroxytryptamine or 5-HT) is a multifunctional bioamine with important signaling roles in a range of physiological pathways. Almost all of the 5-HT in our bodies is synthesized in specialized enteroendocrine cells within the gastrointestinal (GI) mucosa called enterochromaffin (EC) cells. These cells provide all of our circulating 5-HT. We have long appreciated the important contributions of 5-HT within the gut, including its role in modulating GI motility. However, evidence of the physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
168
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(176 citation statements)
references
References 160 publications
4
168
0
4
Order By: Relevance
“…11 The monoamine is distributed by blood platelets throughout the entire body, where it modulates diverse non-neural processes, including various metabolic roles, vascular constriction, platelet aggregation, inflammation, insulin release, intestinal motility, and bladder control. [12][13][14] Behavioral studies in zebrafish have demonstrated the conservation among vertebrates of the different neurological functions of serotonin, as well as of the effects of drugs, which affect the serotonergic system. 15 In zebrafish peripheral organs, serotonin was detected in Merkel-like cells of the taste buds, in neuroepithelial cells of the skin, and joint-associated fibroblasts in the fin.…”
Section: Introductionmentioning
confidence: 99%
“…11 The monoamine is distributed by blood platelets throughout the entire body, where it modulates diverse non-neural processes, including various metabolic roles, vascular constriction, platelet aggregation, inflammation, insulin release, intestinal motility, and bladder control. [12][13][14] Behavioral studies in zebrafish have demonstrated the conservation among vertebrates of the different neurological functions of serotonin, as well as of the effects of drugs, which affect the serotonergic system. 15 In zebrafish peripheral organs, serotonin was detected in Merkel-like cells of the taste buds, in neuroepithelial cells of the skin, and joint-associated fibroblasts in the fin.…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin reduction in plasma was highly significant in obese children. Depression and antidepressant drugs are both associated with increased risk of obesity presumably due to a reduction in serotonin or the serotonin transporter [24,25].…”
Section: Biochemicals Found Only In Plasmamentioning
confidence: 99%
“…Reduced serotonin has been found in cord blood where this reduction was associated with rapid postnatal weight gain [26]. The understanding of serotonin function has been broadly expanded to include obesity and diabetes [25]. (Tables 4 and 5).…”
Section: Biochemicals Found Only In Plasmamentioning
confidence: 99%
“…[11] Exogenous 5-HT significantly attenuates the thermogenic potential of the ÎČ-adrenergic agonist receptor. [12] Bronchodilator drugs are widely used therapeutic agents for the treatment of asthma and COPD. [13,14] The standard treatment of acute severe asthma is the use of short-acting inhaled agonists (SB), systemic corticosteroids and supplemental oxygen.…”
Section: Introductionmentioning
confidence: 99%